Reflections on the Importance of the Leonhardi Euleri Opera Omnia, Volume IV A (2016) and Volume VIII (2018) - Stanisław Domoradzki; Mykhailo Zarichnyi (Studia Historiae Scientiarum)
The article is devoted to two volumes of Leonhard Euler’s correspondence with mathematicians and other scientists.